2020
DOI: 10.1101/2020.05.07.20094227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pandemic related Health literacy – A Systematic Review of literature in COVID-19, SARS and MERS pandemics

Abstract: Background: Health literacy plays an essential role in ones ability to acquire and understand critical medical information in the COVID-19 infodemic and other pandemics. Purpose: To summarize the assessment, levels and determinants of pandemic related health literacy and its associated clinical outcomes. Data sources: Medline, Embase, PsychINFO, CINAHL, arXiv, bioRxiv, medRxiv, and Social Science Research Network. The start date was unrestricted and current as of 22 April 2020. Study selection Studies wh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 92 publications
(213 reference statements)
0
36
1
6
Order By: Relevance
“…(14) Gender and age differences in adherence may be caused by differences such as poorer health literacy in men and a greater desire to be active and to have contact with peer groups amongst younger age groups. (39) Working in a key sector was associated with not self-isolating. This may be because key workers have a greater financial need or feel a greater social pressure to attend work and are less likely to be able to work from home.…”
Section: Discussionmentioning
confidence: 99%
“…(14) Gender and age differences in adherence may be caused by differences such as poorer health literacy in men and a greater desire to be active and to have contact with peer groups amongst younger age groups. (39) Working in a key sector was associated with not self-isolating. This may be because key workers have a greater financial need or feel a greater social pressure to attend work and are less likely to be able to work from home.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review prepared by Seng et al showed that not one of 70 papers included in their analysis evaluated the outcomes associated with HL during epidemics caused by the new, emerging types of coronaviruses. However, researchers had frequently assessed people's knowledge about infections, the resulting worries and the use of preventive measures [88]. After the article by Seng et al was posted online as a preprint on 11 May 2020, more evidence has emerged.…”
Section: Discussionmentioning
confidence: 99%
“…At the top of the ladder are the people who are the best off having more money and best job. The students were asked to think of a ladder as representing where people in their country stand in and they were asked where they would place themselves on this ladder of a ten-point scale (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Methodsmentioning
confidence: 99%